Strengthening the Image of Islamic Schools Through the AIDA Approach: The Role of Public Relations in Engaging the Community - Tantowi, Ahmad; Subchan, Ali; Munadirin, Ahmad; Kadarismanto, Kadarismanto; Muslim, Rifqil (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This research aims to reveal the strategy of public relations in building the image of Madrasah. The research was conducted at Madrasah Aliyah NU 05 Gemuh, using a qualitative approach and triangulation techniques. Data collection was carried out through interviews, observations, and field observations. Sources of informants involved school principals, public relations, teachers, and student parents. The research results show that the public relations manager's strategy in building the Madrasah image involves the